2020
DOI: 10.21315/tlsr2020.31.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fusarium Wilt Disease of Cucumber (Cucumis sativus Linn) in Peninsular Malaysia Caused by Fusarium oxysporum and F. solani

Abstract: Fusarium wilt disease is one of the most problematic and destructive disease in cucumber production. The causative agents are Fusarium oxysporum and F. solani. These pathogens are soil borne and transmitted through infested soil and water. A field survey was conducted to study the disease prevalence in the major growing areas of cucumber in Peninsular Malaysia. Field study revealed that the disease was highly prevalence in the field with the disease incidence was in the range of 10%–60%. The morphological prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The vegetable crops like cucumber can be produced year-round in open fields or greenhouses. Fusarium wilt disease is indeed a significant problem in cucumber production and can have devastating effects on cucumber plants and cause considerable economic losses for farmers, which impairs both yields and fruit quality (Al-Tuwaijri, 2015 ; Din et al, 2020). Cucumber Fusarium wilt was highly prevalence in Babylon Province, with field disease incidence ranging from 22% to 55.3%.…”
Section: Pathogenicitymentioning
confidence: 99%
See 3 more Smart Citations
“…The vegetable crops like cucumber can be produced year-round in open fields or greenhouses. Fusarium wilt disease is indeed a significant problem in cucumber production and can have devastating effects on cucumber plants and cause considerable economic losses for farmers, which impairs both yields and fruit quality (Al-Tuwaijri, 2015 ; Din et al, 2020). Cucumber Fusarium wilt was highly prevalence in Babylon Province, with field disease incidence ranging from 22% to 55.3%.…”
Section: Pathogenicitymentioning
confidence: 99%
“…This disease can devastate cucumber plants and cause considerable economic losses for farmers. The disease is prevalent in most countries, with yield losses ranging from 40-70% (Din et al, 2020;Sharma and Shukla, 2021). According to Fareed et al (2016 ), the cucumber wilt is common in most of the world's cucumber-growing regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This ailment, attributed to Fusarium oxysporum f. sp. cucumerinum , as noted by Din et al, 18 has been identified as a substantial threat. Meng et al 19 have reported that Fusarium wilt thrives in elevated air and soil temperatures (ranging from 23.9 °C to 30 °C), with disease manifestation being less likely in cooler soil conditions (below 20 °C), where an infected plant might remain symptom-free.…”
Section: Introductionmentioning
confidence: 96%